Work organisation, bullying and intention to leave in the hospitality industry. Issue 4 (5th June 2017) - Bohle, Philip; Knox, Angela; Noone, Jack; Mc Namara, Maria; Rafalski, Julia; Quinlan, Michael
Abstract : Purpose: The purpose of this paper is to examine relationships between work organisation, bullying and intention to leave (ITL) in the Australian hospitality industry, using pressure, disorganisation and regulatory failure (PDR) to measure work organisation. Design/methodology/approach: Cross-sectional survey data were collected from 72 workers in Australian accommodation hotels. They were aged 20-65 years ( M =38.26, SD=12.60) and 57.1 per cent were female. The proposed path model was tested with the Mplus (v.7) statistical package using Hayes' (2009) procedure for mediation analysis. Findings: There were positive bivariate correlations between all variables. The path model indicated that disorganisation and regulatory failure had direct positive associations with bullying. Financial pressure and bullying had direct positive associations with ITL. Research limitations/implications: The small sample may not be representative and the cross-sectional design and self-report data risk common method variance effects and preclude attributions of causality. Future studies should use more representative samples and longitudinal designs to address common method variance issues and facilitate causal inferences. Originality/value: Bullying and turnover are significant problems in the hospitality industry, but the contribution of work organisation variables is poorly understood. The present study provides promising preliminary evidence on the potential role of PDR as an antecedent of both bullying and ITL.